2010
DOI: 10.1016/j.jpba.2009.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a stability-indicating HPLC-UV method for the determination of alizapride and its degradation products

Abstract: A stability-indicating high-performance liquid chromatography procedure has been developed for the determination of alizapride (AL) and its main degradation products alizapride carboxylic acid (AL-CA) and alizapride N-oxide (AL-NO2) in drug substance and product. The method was developed based on forced degradation data obtained by HPLC-MS analysis. Indeed AL underwent chemical degradation by acid/base catalyzed hydrolysis and oxidation the main degradation products being AL-CA and AL-NO2 respectively. The sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Alizapride hydrochloride ( AL ) was obtained as gift sample from Pharmafar S.r.l. (Torino, Italy); 6‐methoxy‐1 H ‐benzotriazole‐5‐carboxylic acid 1 and 6‐methoxy‐ N ‐{[1‐oxy‐1‐(prop‐2‐en‐1‐yl)pyrrolidin‐2‐yl]methyl}‐1 H ‐benzotriazole‐5‐carboxamide (diastereomers A 4 and B 5) were synthesized according to the procedure cited in the literature . 6‐Hydroxy‐ N ‐{[1‐(prop‐2‐en‐1‐yl)pyrrolidin‐2‐yl]methyl}‐1 H ‐benzotriazole‐5‐carboxamide 6 was synthesized as previously reported …”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Alizapride hydrochloride ( AL ) was obtained as gift sample from Pharmafar S.r.l. (Torino, Italy); 6‐methoxy‐1 H ‐benzotriazole‐5‐carboxylic acid 1 and 6‐methoxy‐ N ‐{[1‐oxy‐1‐(prop‐2‐en‐1‐yl)pyrrolidin‐2‐yl]methyl}‐1 H ‐benzotriazole‐5‐carboxamide (diastereomers A 4 and B 5) were synthesized according to the procedure cited in the literature . 6‐Hydroxy‐ N ‐{[1‐(prop‐2‐en‐1‐yl)pyrrolidin‐2‐yl]methyl}‐1 H ‐benzotriazole‐5‐carboxamide 6 was synthesized as previously reported …”
Section: Methodssupporting
confidence: 80%
“…(Torino, Italy); 6-methoxy-1H-benzotriazole-5-carboxylic acid 1 and 6-methoxy-N-{[1-oxy-1-(prop-2-en-1-yl)pyrrolidin-2-yl]methyl}-1Hbenzotriazole-5-carboxamide (diastereomers A 4 and B 5) were synthesized according to the procedure cited in the literature. [14] 6-Hydroxy-N-{[1-(prop-2-en-1-yl)pyrrolidin-2-yl]methyl}-1H-benzotriazole-5-carboxamide 6 was synthesized as previously reported. [15]…”
Section: Reagents and Chemicalsmentioning
confidence: 99%
“…The stability of alizapride has already been tested alone or in association with different drugs. [3][4][5][6] As well, the stability of ondansetron alone has been challenged in different containers, 7 at different temperature 8 and in association with various drugs. [9][10][11] Thoses studies showed a stability up to 3 months for ondansetron and up to 32 days for alizapride in several conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported methods for determination of ALZ use liquid-liquid extraction [2][3][4]6,7 or lack IS. 6,7 Tamaro et al 8 reported an HPLC method with UV detection for the determination of ALZ in drug powder and drug product. Sample preparation method is a key step in bioanalytical method development that leads to improved selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%